Reducing the Danger of Landslides by Increasing Land Conservation and Fertility Efforts in Balai Gadang Village, Koto Tangah District, Padang City: Mengurangi Bahaya Longsor Dengan Meningkatkan Usaha Konservasi Dan Kesuburan Lahan Di Kelurahan Balai Gadang, Kecamatan Koto Tangah, Kota Padang - Wilis, Ratna; Edial, Helfia; Yulfa, Arie; Tasman, Abel (Sumatra Journal of Disaster, Geography and Geography Education, 2025)
The large volume of erosion that will result will cause the loss of the top soil layer and a decrease in soil nutrients. For this reason, soil conservation efforts are needed to ensure that the soil is not dispersed, regulate the force of movement and the amount of surface flow so that soil uplift does not occur. This research includes qualitative research where to get data you have to go into the field by discussing with the community. The approach method offered in solving partner problems is as follows: 1) Direct discussions with the people of Balai Gadang Subdistrict whose area is prone to landslides, 2) Training on the use of fruit waste for eco-enzymes and decomposers, as well as vegetative conservation on existing land. The results of this third year of service include: (1) discussions with farmers regarding the manufacture of decomposers and eco enzymes (2) Survey activities to increase agricultural and livestock activities, (3) Conducting training and practice in making decomposers from rice washing water (4) ) Practice of making Eco-enzyme from fruit peel waste, (5) Refresher discussions on farmer group organizations, (6) Practicum with students to check agricultural land fertility, (7) Survey at the new Landslide location for vegetative conservation activities with black bamboo plants, banana, sugar palm, areca nut, vetiver and others